ANALYSIS OF THE ATTRACTIVENESS AND COMPETITIVENESS OF THE SECURITIES MARKET IN LITHUANIA - Urbšienė, Laimutė; Monkevičiūtė, Rūta; Navikaitė, Urtė (Ekonomika, 2014)
The importance of attractiveness and competitiveness of the Lithuanian stock market has significantly increased in the recent years due to its influence on the capital market as well as on its participants and the economy of the whole country. This article aims to evaluate the attractiveness and competitiveness of Lithuania’s securities market by using a quantitative analysis. It has aimed to define the statistically significant relationship between market attractiveness and competitiveness and the number of listed companies, cross listing, liquidity and trade volumes. The quantitative analysis has provided arguments to conclude that securities market in Lithuania currently is not attractive either from the point of capital supply or from the point of capital demand. In addition, the securities market in Lithuania lacks competitiveness among other markets.